2014
DOI: 10.1371/journal.pone.0095368
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Expression of a Novel Alcohol Oxidase from Aspergillus terreus MTCC6324

Abstract: The alcohol oxidase (AOx) cDNA from Aspergillus terreus MTCC6324 with an open reading frame (ORF) of 2001 bp was constructed from n-hexadecane induced cells and expressed in Escherichia coli with a yield of ∼4.2 mg protein g−1 wet cell. The deduced amino acid sequences of recombinant rAOx showed maximum structural homology with the chain B of aryl AOx from Pleurotus eryngii. A functionally active AOx was achieved by incubating the apo-AOx with flavin adenine dinucleotide (FAD) for ∼80 h at 16°C and pH 9.0. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…Black coloured clades were not considered for the analysis. 1—Daniel et al [15]; 2—de Oliveira et al [20]; 3—Linke et al [59]; 4—Cregg et al [14]; 5—Sakai and Tani [79]; 6—Ledeboer et al [55]; 7—Chakraborty et al [13]; 8—Segers et al [81]; 9—Soldevila and Ghabrial [85]
Fig. 4Maximum likelihood tree of the dehydrogenase domains in the cellobiose dehydrogenase (CDH) cluster.
…”
Section: Resultsmentioning
confidence: 99%
“…Black coloured clades were not considered for the analysis. 1—Daniel et al [15]; 2—de Oliveira et al [20]; 3—Linke et al [59]; 4—Cregg et al [14]; 5—Sakai and Tani [79]; 6—Ledeboer et al [55]; 7—Chakraborty et al [13]; 8—Segers et al [81]; 9—Soldevila and Ghabrial [85]
Fig. 4Maximum likelihood tree of the dehydrogenase domains in the cellobiose dehydrogenase (CDH) cluster.
…”
Section: Resultsmentioning
confidence: 99%
“…Since the first report in 1960 by Farmer et al ( 1960 ), who identified aromatic alcohol oxidase activity in the growth medium of the basidiomycete Polystictus (Trametes) versicolor , AAO activity has been found in cultures of many other basidiomycetes like Pleurotus species (Bourbonnais and Paice 1988 ; Galperin et al 2016 ; Guillen et al 1990 ; Sannia et al 1991 ; Varela et al 2000 ), Bjerkandera adusta (Muheim et al 1990b ; Romero et al 2009 ), Bjerkandera sp. BOS55 (de Jong et al 1992a ), Coprinopsis cinerea (Tamaru et al 2018 ), Phanerochaete chrysosporium (Asada et al 1995 ), Ustilago maydis (Couturier et al 2016 ), and ascomycetous fungi such as Aspergillus terreus (Chakraborty et al 2014 ), Botrytis cinerea (Goetghebeur et al 1992 ), Fusarium proliferatum (Regalado et al 1999 ), Geotrichum candidum (Kim et al 2001 ), and Thermothelomyces thermophilus (Kadowaki et al 2020 ) . Although predominantly found in fungi, enzymes with AAO activities have also been reported in bacteria Sphingobacterium sp.…”
Section: Occurrence and Gmc Superfamilymentioning
confidence: 99%
“…4B ). Differently, C. cinerea r Cc AAO catalyzed oxidation of both vanillyl alcohol and isovanillyl alcohol with similar activities, which were only slightly lower than activity towards benzyl alcohol (Chakraborty et al 2014 ; Tamaru et al 2018 ). AAO of Bjerkandera BOS55 prefers mono- and dichlorinated anisyl alcohols as substrates (de Jong et al 1994 ).…”
Section: Substrate Spectrummentioning
confidence: 99%
“…Red stars indicate the absence of kinetic data. Abbreviations (and associated references for corresponding data) are as follows: Lac, laccase(380)(381)(382)(383); POD, peroxidase(380,(384)(385)(386)(387)(388); CDH, cellobiose dehydrogenase(102,(128)(129)(130)(389)(390)(391)(392); GOX, glucose oxidase(167,(393)(394)(395)(396)(397)(398); AAO, aryl alcohol oxidase(166,399,400); GDH, glucose dehydrogenase(401,402); AAQO, aryl alcohol quinone oxidoreductase(403); PDH, pyranose dehydrogenase(404)(405)(406)(407); AOX, alcohol oxidase(177,(408)(409)(410); P2O, pyranose 2-oxidase(181,(411)(412)(413); VAO, vanillyl alcohol oxidase(186,187); GLOX, glyoxal oxidase(170,<...>…”
mentioning
confidence: 99%